The North Side Children's Agency (B) : finances versus mission - Donnelly, Anne Cohn; Logue, Trinita ([London] : SAGE, 2016)
The North Side Children's Agency (NSCA) was a nonprofit founded to serve low-income working parents who qualified for income-based government child care subsidies. In support of its mission, the NSCA operated year-round, full-day child care programmes. After years of success, in 2004 the NSCA faced a serious cash shortage and its first deficit in a decade. This case explains how the board members faced up to the issue.
Originally Published in: Donnelly, A. C., & Logue, T. (2012). The North Side Children's Agency (B): Finances versus Mission. 5-112-006(B). Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 29, 2016).
Keywords: elektronické knihy; electronic books; Nonprofit organizations -- Management -- Case studies; Corporate governance -- Case studies